Development of Regenerative Braking Concept for Electric Vehicle Enhanced with Bidirectional Converter - M. Kavitha; V. Elanangai; S. Jayaprakash; V. Balasubramanian (Institute of Advanced Engineering and Science, 2018)
Due to the increasing concern for environment protection and the uncertainty about oil reserves, nowadays electricity is playing a key role as an alternative energy source in the automotive sector. In this paper, non isolated bidirectional converter is used for electric vehicle application during regenerative braking process. During motoring operation, the converter supplies energy to motor through battery. In regenerative braking action, the converter supplies the available back emf to charge the battery. The recycled energy is effectively stored in the battery. The simulation is carried out in MATLAB/Simulink. The worthiness of simulation is illustrated experimentally by developing a prototype. The simulation and experimental results are presented in this paper.